Strain-induced folding on [111]-copper single crystals under uniaxial compression - Lychagin D. V. Dmitry Vasilievich; Tarasov S. Yu. Sergei Yulievich; Chumaevsky A. V. Andrey Vladimirovich; Alferova (Alfyorova) E. A. Ekaterina Aleksandrovna (2016, 2016)
Title screen